Protection of Stateless Persons in International Law and Legislation of the RA - Vardanyan, Qnarik; Ghazinyan, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2022)
The current article discusses the main issues in the international and national legal framework concerning the protection of stateless persons and the reduction of statelessness. The main international and domestic legal acts regulating the field and their effectiveness in detecting stateless persons and providing protection are presented.The real situation concerning stateless persons is not always discussed correctly. They are mainly deprived of all rights that seem usual to us. This makes that “invisible” from the legal perspective. People, who physically exist, are not legally recognized.International documents aimed at the decreasing statelessness establish the universal legal framework. While implementing their regulations, states should establish effective domestic mechanisms to ensure secure and prosperous life for stateless persons living in their territory.
Keywords: International protection of apatrides; #I Belong; RA legislation on citizenship; Конвенция о статусе лиц без гражданства 1954 г; 1954 Convention relating to the status of stateless people